2019
DOI: 10.1002/humu.23906
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing‐based microsatellite instability testing using as few as six markers for high‐throughput clinical diagnostics

Abstract: Microsatellite instability (MSI) testing of colorectal cancers (CRCs) is used to screen for Lynch syndrome (LS), a hereditary cancer‐predisposition, and can be used to predict response to immunotherapy. Here, we present a single‐molecule molecular inversion probe and sequencing‐based MSI assay and demonstrate its clinical validity according to existing guidelines. We amplified 24 microsatellites in multiplex and trained a classifier using 98 CRCs, which accommodates marker specific sensitivities to MSI. Sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Alternatively, MSI assays that enrich and sequence specific microsatellites can be used, keeping costs equivalent to or less than MSI FLA or IHC, whilst leveraging the scalability and automatability of NGS and multiplexed analysis of BRAF c.1799T > A. Such assays can reduce LS screening to one, low cost, high throughput tumour test prior to germline MMR gene testing of select cases, and could facilitate widespread deployment of current guidance [ 127 , 128 , 129 ].…”
Section: The Next Generation Of Ls Screeningmentioning
confidence: 99%
“…Alternatively, MSI assays that enrich and sequence specific microsatellites can be used, keeping costs equivalent to or less than MSI FLA or IHC, whilst leveraging the scalability and automatability of NGS and multiplexed analysis of BRAF c.1799T > A. Such assays can reduce LS screening to one, low cost, high throughput tumour test prior to germline MMR gene testing of select cases, and could facilitate widespread deployment of current guidance [ 127 , 128 , 129 ].…”
Section: The Next Generation Of Ls Screeningmentioning
confidence: 99%
“…These are facilitated by the assay’s low cost, at approximately $15–55 per sample for reagents, and scalability, being fully automatable and able to analyze 7–174 samples on a single MiSeq flow cell (Supplementary Information S 3 ). 25 , 29 In further support of its clinical utility, we have previously validated the MSI assay’s sensitivity and specificity using a blinded sample cohort, 25 and, here, we have demonstrated that it can be deployed in a separate laboratory from the laboratory in which it was developed (including perfect concordance of sample classification between laboratories), shown that control sample scoring is equivalent between laboratories, updated it with automatically flagged QCs based on sequencing metrics, and expanded the reference set of controls to make it more robust (Supplementary Information S 2 ). Therefore, while the MSI assay has not been formally accredited for clinical diagnostics, its performance in this study suggests it may not only be useful in research, but also in clinical settings as a prescreening assay on selected individuals or to resolve diagnostic uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while the MSI assay has not been formally accredited for clinical diagnostics, its performance in this study suggests it may not only be useful in research, but also in clinical settings as a prescreening assay on selected individuals or to resolve diagnostic uncertainties. 18 , 25 , 29 Having shown the feasibility of large-scale MSI analysis to screen for CMMRD, the prevalence of CMMRD in other patient groups could be defined using this screening pipeline. This is particularly important given the broad phenotypic spectrum of CMMRD, including the wide variety of associated cancer types, and the clinical implications of its differential diagnosis with respect to clinical surveillance, therapy, and genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations